(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
Basin margin sedimentary deposits are increasingly recognized as holding significant potential for both hydrocarbon source and reservoir rocks, depending largely on the prevailing paleogeographic and depositional conditions. Despite their importance, the depositional environments of sedimentary successions along the eastern margin of the Bida Basin, particularly around Lapai, have not been systematically documented. This study addresses that gap by examining part of the eastern margin basin fill through detailed field investigations and facies analysis of relatively well-exposed outcrops. The analysis led to the recognition of seven lithofacies, which were further grouped into three genetically related facies associations: (i) offshore lacustrine, (ii) subaqueous fan-delta, and (iii) subaerial fan systems. The offshore lacustrine association is dominated by mudstone facies (Fm), massive sandstone (Sm), and normally graded gravelly sandstone (Sn). These facies are interpreted as the products of suspension settling, hyperconcentrated density flows, and turbidity currents, respectively. The subaqueous fan-delta association is characterized by the intercalation of debris-flow deposits (Facies Gmu, Sm, and Sn) with fine-grained mudstone and siltstone intervals (Fm), reflecting the interplay between mass-flow processes and background lacustrine sedimentation. In contrast, the subaerial fan association is represented predominantly by ungraded, matrix-supported conglomerates (Gmu) and pebbly to massive sandstones (Sm), with occasional trough cross-bedded conglomerates (Gt) and minor mudstone intercalations (Fm). The observed vertical stacking pattern of these associations indicates a progressive progradation of alluvial fan systems into the lacustrine environment, reflecting a dynamic interplay between tectonic activity, sediment supply, and lake-level fluctuations along the basin margin. From a petroleum system perspective, the subaqueous fan-delta association is interpreted as the most prospective target for conventional hydrocarbon reservoirs, owing to its textural heterogeneity and potential for sand-rich channelized deposits. Meanwhile, the offshore lacustrine facies association holds significant potential for unconventional hydrocarbon resources, especially as organic-rich fine-grained intervals could act as both source rocks and tight reservoirs. Overall, this work underscores the importance of integrating detailed outcrop-based facies analysis with paleoenvironmental reconstructions to generate robust conceptual paleogeographic models. Such models are invaluable in assessing the petroleum potential of basin-margin successions, particularly in underexplored frontier basins like the Bida Basin.